2019
DOI: 10.1007/s12046-019-1151-8
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of axial wall conduction in a microtube subjected to two classical thermal boundary conditions

Abstract: Heat transfer in laminar flow microtube is numerically explored with an objective of discriminating conjugate heat transfer process experienced in a microtube under two different thermal conditions. Two classical thermal conditions-constant heat flux and constant wall temperature-are imposed separately on the outer surface of a microtube. Wide parametric variations are considered in this study, for the two thermal conditions, albeit the problem under consideration being very classical from both geometry and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Microchannel heat sink facilitates liquid cooling with higher surface area to volume ratio but simultaneously accompanied with excessive pressure drop limiting the application to low flow rate laminar flows. The substrate material significantly affects the conjugate heat transfer process and was demonstrated that phase change phenomenon in microchannel significantly improves thermal performance (Tiwari and Moharana, 2019a, 2019c). Thus, to enhance cooling, it becomes necessary to either improve fluid and heat sink material properties or somehow change the flow behaviour to enhance convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Microchannel heat sink facilitates liquid cooling with higher surface area to volume ratio but simultaneously accompanied with excessive pressure drop limiting the application to low flow rate laminar flows. The substrate material significantly affects the conjugate heat transfer process and was demonstrated that phase change phenomenon in microchannel significantly improves thermal performance (Tiwari and Moharana, 2019a, 2019c). Thus, to enhance cooling, it becomes necessary to either improve fluid and heat sink material properties or somehow change the flow behaviour to enhance convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%